Effects of a Physically Active Lifestyle Modification (PALM) Program for Independent Taiwanese Older Adults: A Mixed-Methods Pilot Study. Issue 2 (April 2022) - Kuo, Chang-Chih; Shyu, Hui-Jen; Park, Daniel; Tsai, Pei-Chun; Li, Yu-Hsien
Abstract : This pilot study investigated a manualized lifestyle-based intervention, Physically Active Lifestyle Modification (PALM) program, designed to increase physical activity in the daily life routines of Taiwanese older adults and improve their quality of life. Thirty older adults who attended a Senior Citizens Learning Camp in Taiwan participated in the program. Quantitative measures and qualitative interviews were employed to study the intervention's effect on quality of life and to capture participants' subjective experiences in the program. Results revealed significant improvement in both physical and mental component summary of the RAND 36-Item Short Form Health Survey. Interview data revealed 4 key themes: change in action, self-awareness of occupational pattern, acquisition of health information, and social participation.